Antibiotic use in Kenyan public hospitals: Prevalence, appropriateness and link to guideline availability. (October 2020) - Maina, Michuki; Mwaniki, Paul; Odira, Edwin; Kiko, Nduku; McKnight, Jacob; Schultsz, Constance; English, Mike; Tosas-Auguet, Olga
Highlights: We report findings from a point prevalence survey across 14 Kenyan public hospitals. About half of the hospitalised patients received appropriate antibiotic therapy. Laboratory investigations supported less than 1% of the antibiotic prescriptions. Physical availability of treatment guidelines influenced treatment appropriateness. There is need for context-specific, up-to-date, and accessible treatment guidelines. Abstract: Objective: To examine prescription patterns and explore to what extent guidelines are available and how they might influence treatment appropriateness among hospitalised patients in Kenyan hospitals. Methods: Data on antimicrobial usage were collected from hospitalised patients across 14 Kenyan public hospitals. For each prescription, appropriateness of treatment was defined using available local and international treatment guidelines and through consensus with local medical specialists. Association between appropriate treatment, guideline availability and other possible explanatory factors was explored using univariate and multiple regression analysis. Results: There were 1675 (46.7%) of the 3590 hospitalised patients on antimicrobials with 3145(94%) of the 3363 antimicrobial prescriptions being antibiotics. Two patients (0.1%), had treatment based on available antibiotic susceptibility tests. Appropriate treatment was assessed in 1502 patients who had a single diagnosis. Of these, 805 (53.6%) received appropriate treatment. Physical availability of treatment guidelines increased the odds of receiving appropriate treatment Odds Ratio 6.44[95% CI 4.81–8.64]. Conclusion: Appropriate antibiotic prescription remains a challenge in Kenyan public hospitals. This may be improved by the availability of context-specific, up-to-date, and readily accessible treatment guidelines across all the departments, and by providing better diagnostic support.